2020
DOI: 10.1111/andr.12765
|View full text |Cite
|
Sign up to set email alerts
|

Late‐onset hypogonadism and lifestyle‐related metabolic disorders

Abstract: Background Late‐onset hypogonadism (LOH) is a condition defined by low levels of testosterone (T), occurring in advanced age. LOH is promoted by senescence, which, in turn, has negative effects on male fertility. Interestingly, the impact of metabolic disorders on the male reproductive system has been the topic of several studies, but the association with LOH is still debatable. Objectives Herein, we discuss the hypothesis that the prevalence of metabolic abnormalities potentiates the effects of LOH on the mal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
8
0
3

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 28 publications
(12 citation statements)
references
References 74 publications
1
8
0
3
Order By: Relevance
“…Among women, the associations of DHEA and DHEAS with CVD have also been found to be inconsistent (11)(12)(13). Additionally, diabetes has adverse effects on the reproductive system and sex hormones and increases the frequency of hypogonadism (14,15). The risk of CVD among patients with diabetes is twice that of non-diabetic men and three times that of non-diabetic women (16).…”
Section: Introductionmentioning
confidence: 99%
“…Among women, the associations of DHEA and DHEAS with CVD have also been found to be inconsistent (11)(12)(13). Additionally, diabetes has adverse effects on the reproductive system and sex hormones and increases the frequency of hypogonadism (14,15). The risk of CVD among patients with diabetes is twice that of non-diabetic men and three times that of non-diabetic women (16).…”
Section: Introductionmentioning
confidence: 99%
“…These include obesity, diabetes, and metabolic syndrome and opioid use, among others. 40,[67][68][69][70][71][72][73][74][75][76][77][78][79][80] Therefore, it is irrational to dismiss these newly described conditions and advocate against TTh under the guise of ''age-related'' TD. Moreover, in the clinical setting, ''age-related'' or ''idiopathic'' TD is among the most common etiology noted.…”
Section: Does It Really Matter What Causes Low T?mentioning
confidence: 99%
“…Male hypogonadism is characterized by a deficiency of testosterone, a critical hormone required for sexual, cognitive, and body functions and development [ 1 ]. Studies have found that testosterone deficiency not only affects the quality of life but also increases the risk of erectile dysfunction, metabolic syndrome, diabetes, osteoporosis, fracture, and cardiovascular disease [ 2 7 ]. Studies have also reported that middle-aged and elderly men with low testosterone levels have increased overall mortality and cardiovascular disease mortality rates in long-term follow-up [ 8 12 ].…”
Section: Introductionmentioning
confidence: 99%